2012
DOI: 10.1155/2012/464532
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Costimulatory Receptors of the Tumour Necrosis Factor Receptor Family in Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease that is mediated by both the innate and adaptive immune responses. T lymphocytes, that together with B cells are the cellular effectors of the adaptive immune system, are currently endowed with crucial roles in the development and progression of atherosclerosis. Costimulatory receptors are a class of molecules expressed by T lymphocytes that regulate the activation of T cells and the generation of effector T-cell responses. In this review we present the roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 169 publications
(212 reference statements)
0
9
0
1
Order By: Relevance
“…Moreover, a study on a small group of RA patients showed that Abatacept did no alter the frequency of CD4 + CD28 null T cells in RA patients on long‐term therapy with this drug (> 5 years), suggesting that any effects on this cell subset induced by Abatacept may be transient or the mere result of fluctuations in disease activity. In view of our findings that OX40 and 4‐1BB co‐stimulatory receptors are up‐regulated on CD4 + CD28 null T cells in myocardial infarction, targeting these molecules may prove a more successful approach, especially as OX40 and 4‐1BB belong to a different family of co‐stimulatory receptors than CD28 and CTLA‐4 . Clinical targeting of OX40 and 4‐1BB is being investigated in RA, multiple sclerosis, inflammatory bowel disease, asthma, transplantation and graft‐versus‐host disease .…”
Section: Potential Strategies To Target Cd4+cd28null T Cellsmentioning
confidence: 99%
“…Moreover, a study on a small group of RA patients showed that Abatacept did no alter the frequency of CD4 + CD28 null T cells in RA patients on long‐term therapy with this drug (> 5 years), suggesting that any effects on this cell subset induced by Abatacept may be transient or the mere result of fluctuations in disease activity. In view of our findings that OX40 and 4‐1BB co‐stimulatory receptors are up‐regulated on CD4 + CD28 null T cells in myocardial infarction, targeting these molecules may prove a more successful approach, especially as OX40 and 4‐1BB belong to a different family of co‐stimulatory receptors than CD28 and CTLA‐4 . Clinical targeting of OX40 and 4‐1BB is being investigated in RA, multiple sclerosis, inflammatory bowel disease, asthma, transplantation and graft‐versus‐host disease .…”
Section: Potential Strategies To Target Cd4+cd28null T Cellsmentioning
confidence: 99%
“…Most naive CD4 + T cells constitutively express the co-stimulatory receptor CD28, which delivers vital signals that sustain the proliferation and survival of T cells upon antigen recognition. 6 A subset of CD4 + T cells that lack CD28—known as CD4 + CD28 null (CD28 null ) T cells—has been identified and implicated in several chronic inflammatory diseases, including atherosclerosis. 7 , 8 These cells share features with Th1 cells, but also diverge phenotypically and functionally from conventional CD4 + CD28 + (CD28 + ) Th1 lymphocytes ( Figure 1 ).…”
Section: Cd4 + Cd28 Null T Cellmentioning
confidence: 99%
“… 7 , 9 Noteworthy, CD28 null T cells are more adept at secreting pro-inflammatory cytokines IFN-γ and TNF-α than conventional CD28 + T cells, both in the resting state and following activation. 10 We have recently demonstrated that, in patients with acute coronary syndrome (ACS), CD28 null T-cell cytokine production is regulated by the alternative co-stimulatory receptors OX40 and 4-1BB 6 that were significantly up-regulated on circulating CD28 null compared with CD28 + T cells. 10 In addition, CD28 null T cells express and release cytotoxic molecules perforin and granzyme B.…”
Section: Cd4 + Cd28 Null T Cellmentioning
confidence: 99%
“…A variety of studies have manipulated costimulation via B7/CD28, ICOS/ICOSL, Ox40/Ox40L, CD137 (IBB)/CD137L, CD30/CD30L, CD40-TRAF6/CD40L and PD1/PDL in either the Apoe −/− model or the Ldlr −/− model. In none of these cases has a change in plasma lipid levels been reported [3339]. On the other hand, the LIGHT/lymphotoxin co-stimulatory family, members of the TNFR family, do have an influence on plasma lipids in the Ldlr −/− mice.…”
Section: Influence Of the Adaptive Immune System On Plasma Lipoproteinsmentioning
confidence: 99%